(3eHGfj GdCNHGQ aj TQM eYGfj GdBKGQs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s; (3CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROqj GdWMGhj, CHh LYaQ,J (B321 (3g` s
(3ChdgG (B:s
(3cdGe Ydi GdWhGa s
(3BNQgG (B:s
(3HGH GdQLd jfaj hdO GeQCJg Mjf ojhdO , gd jWYf Hg Ce dG s
(3GdfSNI HgG MhGTs
(3ef GdfSNI faSgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B107s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B95 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1728s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs